Autonomy and capacity: the ethical and legal considerations. Issue 11 (2nd December 2021) - Bifarin, Oladayo; Stonehouse, David
Abstract : This article discusses the important concept of autonomy and what this means for patients and their families. This concept is the first of the four ethical principles identified by Beauchamp and Childress (2019) and is an important legal issue. First, the ethical position of autonomy will be explored, before moving on to discuss the legal aspects. Next, definitions will be presented, and the relevant and pertinent parts of the Nursing and Midwifery Council (NMC) (2018) code introduced. Finally, closely linked to autonomy is capacity. This link will be discussed, highlighting the processes and considerations that need to be considered if a person's capacity is reduced.